Goodbye Heritage, Hello Stranger - Ekvall,David; Carlsson Ramirez,Camilo (2025)
This study explores consumer perceptions of heritage brands following a revolutionary rebrand, with a focus on adapting the Consumer Perceived Value (CPV) theory. Building on Wuestefeld et al.’s (2012) framework, the research incorporates the disruptive nature of revolutionary rebranding to extend the theoretical understanding of CPV in a heritage branding context. Guided by a relativist ontology and social constructionist epistemology, the study uses qualitative methods, drawing on semi-structured interviews analyzed through thematic analysis. The findings highlight five key insights: (1) retaining elements of heritage is crucial during rebranding, (2) loss of heritage weakens emotional attachment, (3) clear communication of improvements post-rebrand is essential, (4) economic value is shaped by the coherence of tangible and intangible brand elements, and (5) revolutionary rebrands may reduce perceived social status. These results offer practical guidance for brand managers considering major brand transformations, emphasizing the importance of preserving heritage elements. Additionally, the study presents an adapted CPV framework as a useful tool for assessing consumer responses to rebranding initiatives.
Keywords: Brand heritage; Heritage brands; Revolutionary rebranding; Rebranding; Consumer perception; Consumer Perceived Value Theory; Jaguar